ENVIRONMENTAL STRESS ON THE REPRODUCTION OF NON-HUMAN PRIMATES - Mashitah Shikh ShikhMaidin (SEAMEO BIOTROP, 2021)
This paper aims to review some highlights on the effects of environmental stress on the non-human primate population, particularly climate change and food limitation, which may have resulted in poor reproductive performance. The International Union for Conservation of Nature (IUCN) lists more than a third of the world’s primates as critically endangered or vulnerable. Non-human primates, which are the closest biological relatives of humans, are threatened with extinction due to human activities and environmental stress. Deforestation is the main problem that intercalates with climate change. Either indirectly or directly, those extinction factors could interrupt the physiological basis of reproduction among non-human primates. Research on other species has shown that high ambient temperature causing heat stress has harmed reproductive performance by interfering with the hypothalamic–pituitary–gonadal axis. Therefore, the survival, conservation, and sustainability of non-human primates growing in captivity and in the wild require more work and research to be done.